Entrepreneurship Education Model of Pesantren on Reducing Unemployment - Siswantoro Siswantoro (EL-TARBAWI, 2022)
Several previous studies have found that entrepreneurship can be alternative to reducing unemployment. Pesantren graduates are considered to have the potential to contribute to the average number of unemployed due to the lack of competence of students. On the other hand, as community-based institutions, many pesantren have potential that can be empowered. Therefore, the purpose of this study is to design a model of entrepreneurship education in pesantren. The research method used is a qualitative type with a literature study approach. The data used in this study are secondary in the form of journal articles, news, government reports, and other relevant sources. The data is then analyzed and integrated with the views of this researcher to produce a new concept in the form of an empowerment model through pesantren entrepreneurship education. The results of this study indicate that the designed model could be a solution to improve the entrepreneurial competence of students. The model consists of four important steps such as identifying business potential, capitalization of capital, capacity building of pesantren managers, and implementation of entrepreneurship education. Implementing the pesantren entrepreneurship education model requires contributions from various stakeholders such as governments, private sectors, communities, and universities.